Thrombolysis in submassive pulmonary embolism, prudent or puerile?. (24th January 2013) - Rehman, Aamer; Yousaf, Shafaq; Chugh, Atul
Abstract : Pulmonary embolism (PE) remains one of the leading causes of cardiovascular mortality. The safety and efficacy of thrombolytic therapy using tissue-type plasminogen activator (tPA) for acute PE in clinical practice remain unclear. We describe a case of life-threatening submassive PE causing extreme refractory hypoxaemia, where thrombolysis was successfully administered. Current consensus suggests that patients with features of hemodynamic instability as a result of an acute PE, that is, massive PE, should receive thrombolysis. Patients, not in shock however, but with evidence of right-ventricular (RV) dysfunction echocardiographically, that is, submassive PE may also benefit. Serum troponin and brain-type natriuretic peptide have been suggested as biomarkers of RV injury that may identify a subset of submassive PE patients who may particularly benefit from thrombolytic therapy. The clinical response of this patient to thrombolysis is important, as it may identify a subgroup of patients with submassive PE who warrant this intervention.